Suspended sediment floc size in the Cam - Nam Trieu estuary (Hai Phong, Vietnam), in wet season - Vinh, Vu Duy; Ouillon, Sylvain; Nguyen, Minh Hai (Vietnam Journal of Marine Science and Technology, 2021)
Median diameters (D50) of suspended particles were inferred in the wet season in the Cam - Nam Trieu estuary (Hai Phong, Vietnam) based on the particle size distribution measured by LISST-100X on five transects along the river from 23 to 26 September 2015. The results showed that floc diameters varied between 3.6 μm to 146.5 μm and averaged 49.14 μm. At high tide, the average floc size D50 was lowest (42.66 ± 11.55 µm). It reached the highest value in the ebb tide (62.87 ± 23.34 µm) and then decreased to intermediate values in the flood tide (48.75 ± 15.72 µm). The coefficient of variation of the mean floc size D50 was lowest in the high tide (27.05%), highest in ebb tide (37.13%), then intermediate in the flood tide (32.12%).